2002
DOI: 10.1182/blood-2002-03-0723
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of TRPC proteins in human platelets: evidence that TRPC6 forms the store-independent calcium entry channel

Abstract: Store-operated Ca ؉؉ entry (SOCE) is thought to comprise the major pathway for Ca ؉؉ entry in platelets. Recently, a number of transient receptor potential (TRP) proteins, which have been divided into 3 groups (TRPC, TRPM, and TRPV), have been suggested as SOCE channels. We report the expression and function of TRPC proteins in human platelets. TRPC6 is found at high levels and TRPC1 at low levels. Using purified plasma (PM) and intracellular membranes (IM), TRPC6 is found in the PM, but TRPC1 is localized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
196
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(216 citation statements)
references
References 67 publications
(86 reference statements)
17
196
3
Order By: Relevance
“…By overexpressing both Fyn and TRPC6, these authors showed association of Fyn with TRPC6 and that Fyn phosphorylated the channel in an in vitro kinase assay. In contrast, in a previous study by Hassock et al (48) endogenous TRPC6 in human platelets challenged with thrombin was found to be a substrate for cyclic AMP-dependent protein kinase but not for tyrosine kinases. Differences in channel protein level when both the channel and the kinase are overexpressed in a heterologous system (47) compared with those found under native conditions (48), may in part account for this discrepancy.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…By overexpressing both Fyn and TRPC6, these authors showed association of Fyn with TRPC6 and that Fyn phosphorylated the channel in an in vitro kinase assay. In contrast, in a previous study by Hassock et al (48) endogenous TRPC6 in human platelets challenged with thrombin was found to be a substrate for cyclic AMP-dependent protein kinase but not for tyrosine kinases. Differences in channel protein level when both the channel and the kinase are overexpressed in a heterologous system (47) compared with those found under native conditions (48), may in part account for this discrepancy.…”
Section: Discussionmentioning
confidence: 44%
“…In contrast, in a previous study by Hassock et al (48) endogenous TRPC6 in human platelets challenged with thrombin was found to be a substrate for cyclic AMP-dependent protein kinase but not for tyrosine kinases. Differences in channel protein level when both the channel and the kinase are overexpressed in a heterologous system (47) compared with those found under native conditions (48), may in part account for this discrepancy. An increasing body of evidence implicates different kinases in regulation of ion channel function in the greater TRP superfamily.…”
Section: Discussionmentioning
confidence: 44%
“…TRPC6 was first reported to be phosphorylated by PKA in human platelets, but this does not appear to alter 1-oleoyl-2-acetyl-glycerol-stimulated calcium influx (104). Similarly, PKA has been reported to inhibit TRPC5 but not TRPC6 currents when the proteins are expressed in 293T cells (105), and activation of TRPC6 by cAMP analogues is insensitive to H89 (99).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic AMP-dependent protein kinase A potentiates TRPV1 by direct phosphorylation (27). TRPC6 is a substrate for protein kinase A, although phosphorylation appears to not affect cation permeation (28). The TRPM7 activity seems to be dependent on the Src family PTKs, although whether TRPM7 is directly phosphorylated by tyrosine kinases or not is unclear (29).…”
Section: Stimulation Of the Egf Receptor Induces Rapid Tyrosine Phospmentioning
confidence: 99%